VILNIUS UNIVERSITY DEPARTMENT OF BOOK SCIENCE IN 1940–1943 - NAVICKIENĖ, AUŠRA (Knygotyra, 2015)
The birth of the Vilnius University Department of Book Science has crowned the attempts of book science founders by institutionalizing the book science in the academic space of Lithuania rather early. This Department was a centre of book science studies and science. Professors of the Department of Book Science were delivering lectures during all four years of the Department’s existence, and in the period of 1942–1943 students took a program of Book Science that could be called the first university program of Book Science studies. Regardless of the fact that there was only one group of graduates of these studies, a new independent qualification of book scientist was included in the list of specialists of Lithuanian universities. Scientific aspirations, large ambitions and potential, as well as demand for dispersion of books science scientific works of the personnel of the Department of Book Science have been demonstrated by their intention to publish a scientific book science journal “Bibliotheca Lituana”. But because of unfortunate circumstances the scientific articles that were prepared for the publication and that covered a broad scope of Book Science problems and reflected a quite large group of researchers stayed in manuscripts. In 1943 the activity of the Department of Book Science stopped, and so did the development of Book Science in Lithuania. During the second soviet occupation like-minded persons of V. Biržiška, who stayed in Lithuania have tried to re-establish the former book science institutions at universities of Lithuania, but, alas, unsuccessfully. Because of changes in the situation of this science in Russia, Lithuania moved away from traditional problems of book science up to 1960 and only in 1990 an academic unit that was responsible for book science as a theoretical and applied science, which investigated a book, book publishing, book production and book distribution combined, as well as research and studies was re-established.